Foreign and travel journalism on West Papua: The case of the Swedish press - Petersson, Thomas (Pacific Journalism Review, 2013)
This article analyses the characteristics of a considerable part of the foreign and travel journalism on West Papua that was published in Swedish press during the period 1959-2009. The analysed material comprises press items, articles, and reports on West Papua published in 27 different Swedish newspapers and periodicals. The comprehensive frame identified in the material is West Papua viewed as a primitive country. Four frames, characteristic of this general frame, are found in the foreign and travel journalism: 1) the primitive Others as dangerous and destructive; 2) the primitive Others as victims; 3) the primitive Others as admirable; and 4) the primitive Others as timeless and unchangeable. In the foreign and news material, a clear élite and big power perspective is apparent, which has been fundamental for when the conflict in West Papua is brought up on the journalistic agenda, and when it is not. A power fortifying integration between the frame of West Papua as a primitive country, and the élite and big power perspective exist in the material that during the entire time period covered by this investigation, has resulted in the Papuans being made invisible, and/or maintaining the Papuans and the conflict in West Papua as something odd, not holding a high value.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYxOWkxLjI0NQ